Analisis Faktor-Faktor yang Mempengaruhi Kinerja Ekspor Indonesia Tahun 1990-2024 - Arriska Salma Rosyidah; Siti Aisyah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
This study aims to analyze the effects of Gross Domestic Product (GDP), exchange rates, and interest rates on Indonesia export performance during the period 1990-2024. The data used are secondary data obtained from the Badan Pusat Statistik (BPS), World Bank, and Bank Indonesia (BI), comprising a total of 35 annual observations. This study employs a quantitative approach using a time series regression model estimated by the Ordinary Least Squares (OLS) method. The estimation results indicate that GDP, exchange rates, and interest rates have a positive and significant effect on Indonesia exports. These findings highlight the importance of maintaining exchange rate stability, increasing production capacity, and implementing conducive monetary policies to promote sustainable export growth..